Pengaruh City Branding dan City Image Terhadap Keputusan Berkunjung Wisatawan di Objek Wisata Bahari Kawasan Mandeh Kabupaten Pesisir Selatan Provinsi Sumatera Barat - Rafi Ajis; Ridar Hendri; Trisla Warningsih (Jurusan Sosial Ekonomi Perikanan, 2022)
The purpose of this study was to determine the effect of City Branding and City Image on the decision to visit tourists in the marine tourism object in the Mandeh area. The research method used in this study was a quantitative research method using primary data and secondary data. The population in this study are tourists who have visited and have visited, sampling using a non-probability technique, namely purposive random sampling on tourists from the Mandeh area of ​​Pesisir Selatan Regency with a sample of 100 people. The results showed that City Branding had a direct and significant effect on City Image with a percentage of 49.1%. City Branding on the decision to visit has a significant effect of 13.6% and City Image on the decision to visit is significant at 10.5%.